Production of Mixed Dry Starter from Lactic Acid Bacteria and Saccharomyces cereviceae for Cereal Fermentation - Putri, Widya Dwi Rukmi; Zubaidah, Elok; Maria, M. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2003)
The aims of this research is to gain combination of microbes (Lactic Acid Bacteria and Saccharomyces cereviceae) and the kind of filler that produce dry starter with highest viability. The experiment is carried out in a Randomized Block Design with two factors. First factor, the combination of microbes i.e, Lactobacillus plantarum : Saccharomyces cereviceae 1 : 1 (sel/ml) and Lactobacillus bulgaricus : Saccharomyces cereviceae 1 : 1 (sel / ml). Second factors,Â the kinds of filler i.e, rice flour, wheat flour and combination of rice and wheat flour. The result shows that dry starter from combination ofÂ Lactobacillus bulgaricus : Saccharomyces cereviceae 1 : 1 (sel / ml ) and filler from mixed rice flour and wheat flour have the highest viability for cereal fermentation. Â Keyword: cereal, fermentation